Strategi Komunikasi Marketing Public Relations Barli Coffee - Agung Priyono; Dadi Ahmadi (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Barli Coffee, one of the Coffee Shops in the city of Bandung, which is adjacent to the Art Museum, has a different concept from other Coffee Shop concepts. Entering the era of globalization, competition in various fields is getting real. The success of the performance of Public Relations as an important item of the organization or company tasked with creating and maintaining a positive value or image of the organization is getting higher. When viewed from the marketing mix carried out by Barli Coffee, there are several marketing mixes that are applied to the marketing strategy process at Barli Coffee, namely the initial marketing strategy, which was carried out in the first month by Barli, namely doing live music. The second marketing strategy, which Barli Coffee Shop does is to carry the concept of